2017
DOI: 10.1016/j.jtcvs.2017.04.089
|View full text |Cite
|
Sign up to set email alerts
|

Operative strategies to reduce cerebral embolic events during on- and off-pump coronary artery bypass surgery: A stratified, prospective randomized trial

Abstract: OBJECTIVES The purpose of this study was to determine the impact of different aortic clamping strategies on the incidence of cerebral embolic events during coronary artery bypass grafting(CABG). METHODS From 2012–2015, 142 patients with low-grade aortic disease (epiaortic ultrasound grade I /II) undergoing primary isolated CABG were studied. Those undergoing off-pump CABG were randomized to a partial clamp (n=36) or clampless facilitating device (CFD, n=36) strategy. Those undergoing on-pump CABG were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…The effect of using clamp-less anastomosis devices on cerebral embolic events was directly related to the number of devices used. 26 The present study is not exempted from several limitations, even if this is a large study evaluating the impact of EAU in patients undergoing CABG. First, data on the severity and sites of atherosclerosis in the ascending aorta were not recorded in this registry and cannot be retrieved retrospectively.…”
Section: Commentmentioning
confidence: 97%
See 1 more Smart Citation
“…The effect of using clamp-less anastomosis devices on cerebral embolic events was directly related to the number of devices used. 26 The present study is not exempted from several limitations, even if this is a large study evaluating the impact of EAU in patients undergoing CABG. First, data on the severity and sites of atherosclerosis in the ascending aorta were not recorded in this registry and cannot be retrieved retrospectively.…”
Section: Commentmentioning
confidence: 97%
“…25 Concerns exist regarding the increased amount of embolic debris with the use clamp-less anastomosis devices compared with side-bite clamping in patients undergoing off-pump coronary surgery. 26 In patients without or low-grade atherosclerosis of the ascending aorta, Halkos and colleagues 26 observed that the number of high-intensity transient signals in the middle cerebral arteries was significantly larger with the use of clamp-less anastomosis devices than with side-bite clamping. The effect of using clamp-less anastomosis devices on cerebral embolic events was directly related to the number of devices used.…”
Section: Commentmentioning
confidence: 99%
“…The quest to reduce stroke after CABG has led to numerous observational and prospective trials with a variety of approaches, including off-pump CABG, anaortic approaches, hybrid revascularization, and CFDs. With regard to my group's recent prospective, randomized trial, 1 we agree with Formica and colleagues that there were limitations with our study, specifically that the primary end point was a surrogate for stroke, transcranial Doppler high-intensity transient signals (HITS) rather than a hard clinical end point. Nonetheless, we anticipated a reduction in HITS in the CFD group, supporting the use of these devices, but the results did not support our hypothesis.…”
Section: Clamplessmentioning
confidence: 68%
“…In their prospective randomized study, Halkos and colleagues 1 highlight a strategy to reduce the risk of cerebral embolism during on-pump and off-pump aortic coronary bypass grafting (CABG) surgery. The authors compared 4 groups of patients according to the surgical technique used.…”
Section: Clamplessmentioning
confidence: 99%
“…The reasons for this increase are probably related to small pieces of aortic tissue released during the cutting portion of the procedure. 6 As time marches on, the surgical care of patients with aortic atherosclerosis and severe coronary disease or aortic stenosis is improving, allowing surgeons to offer a safe and atraumatic intervention. Analysis of data such as these should still be performed in a randomized fashion, because blinding is not possible.…”
mentioning
confidence: 99%